Disruption of thrombospondin‐2 accelerates ischemic fracture healing. Issue 6 (31st December 2012) - Miedel, Emily; Dishowitz, Michael I.; Myers, Marc H.; Dopkin, Derek; Yu, Yan‐Yiu; Miclau, Ted S.; Marcucio, Ralph; Ahn, Jaimo; Hankenson, Kurt D.
Abstract Thrombospondin‐2 (TSP2) is a matricellular protein that is highly up‐regulated during fracture healing. TSP2 negatively regulates vascularity, vascular reperfusion following ischemia, and cutaneous wound healing. As well, TSP2‐null mice show increased endocortical bone formation due to an enhanced number of mesenchymal progenitor cells and show increased cortical thickness. Mice deficient in TSP2 (TSP2‐null) show an alteration in fracture healing, that is unrelated to their cortical bone phenotype, which is characterized by enhanced vascularization with a shift towards an intramembranous healing phenotype; thus, we hypothesized that there would be enhanced ischemic fracture healing in the absence of TSP2. We investigated whether an absence of TSP2 would enhance ischemic fracture healing utilizing Laser doppler, µCT and histological analysis. Ischemic tibial fractures were created in wildtype (WT) and TSP2‐null mice and harvested 10, 20, or 40 days post‐fracture. TSP2‐null mice show enhanced vascular perfusion following ischemic fracture. At day 10 post‐fracture, TSP2‐null mice have 115% greater bone volume than WT mice. This is associated with a 122% increase in vessel density, 20% increase in cell proliferation, and 15% decrease in apoptosis compared to WT. At day 20, TSP2‐null mice have 34% more bone volume, 51% greater bone volume fraction, and 37% more bone tissue mineral density than WT. By 40 days after fracture the TSP2‐null mice have a 24% increase in bone volume fraction, but other parameters show no significant differences. These findings indicate TSP2 is a negative regulator of ischemic fracture healing and that in the absence of TSP2 bone regeneration is enhanced. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31: 935–943, 2013